Model development and controller design for DC–DC Boost converters in BCM with parallel cellular architecture - Marcelo, Alexandre Borges [UNESP]; Gonçalves, Flávio Alessandro Serrão [UNESP]; Marafão, Fernando Pinhabel [UNESP] (Elsevier, 2021)
This paper deals with the development and evaluation of mathematical models related with Boost type DC–DC converters operating in Boundary Conduction Mode, including the expansion to a parallel cellular architecture considering the interleaved technique. Initially, an average value-based approach was applied to derive the mathematical models for the three available modes of operation (CCM, DCM and BCM), employing its classic form, which considers the duty cycle disturbance while maintaining a constant switching frequency, and its adherences in describing the behavior due to the BCM's frequency variation. Afterward, an innovative model based on the disturbance in the switching period is proposed for BCM condition. The proposed models were analyzed in different complexity levels, divided into two transfer function orders, referred as reduced and full order. The developed models considering the operation of a single converter were extended to a parallel architecture of N converters. The modes of operation in DCM and BCM were adopted to allow the developed models’ analysis, as well as evaluate and design the converter's operation, where PI controllers were employed. The simulations were executed in the MATLAB software's Simulink environment, with the system implemented by models through subsystems and embedded functions and by switching circuits with assistance of the SymPowerSystems toolbox.
Keywords: Averaged value models; Interleaving; Parallel architecture of DC–DC converters; Step-up DC–DC converters; Voltage mode control